The Role of Islamic Religious Education in Shaping Legal Awareness among Muslim Communities: An Analysis from the Perspectives of Islamic Law and Indonesian Positive Law - Azmi, Muhammad Faisal; Iqbal, Muhammad; Zulfiani, Zulfiani; Khadafi, Andi; Rusli, Rusli (Locus Journal of Academic Literature Review, 2025)
This study explores the strategic role of Islamic Religious Education (Pendidikan Agama Islam/PAI) in shaping legal awareness among Muslim communities in Indonesia, a nation where Islamic legal norms coexist with a comprehensive system of positive law. Legal awareness is a fundamental element in sustaining social order, strengthening obedience to law, and promoting harmony between religious obligations and national legal frameworks. Adopting a qualitative, literature-based research design, this study employs a normative legal approach supported by secondary data drawn from classical and contemporary Islamic legal sources, statutory regulations, and relevant academic literature. The analysis yields three significant findings. First, a noticeable gap remains between the normative ideals embedded in PAI curricula and the actual legal behavior exhibited within Muslim communities. Second, the internalization of legal principles is often constrained by cultural patterns, social habits, and structural limitations that dilute the pedagogical impact of PAI. Third, the effectiveness of PAI in fostering legal consciousness can be strengthened through integrated juridical, educational, and socio-cultural strategies that align Islamic values with the objectives of Indonesian positive law. Overall, this study highlights the transformative potential of PAI as a bridging instrument that harmonizes Islamic legal ethics with state law, thereby contributing to a more legally aware and socially responsible Muslim society.